2014
DOI: 10.1007/s13280-014-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution in urban ecosystems

Abstract: Urban ecologists have demonstrated that cities are functioning ecosystems. It follows then that species living in these contexts should participate in and experience the same suite of biological processes, including evolution, that have occupied scientists for centuries in more "natural" contexts. In fact, urban ecosystems with myriad novel contexts, pressures, and species rosters provide unprecedentedly potent evolutionary stimuli. Here, we present the case for studying adaptive evolution in urban settings. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(161 citation statements)
references
References 63 publications
3
156
0
2
Order By: Relevance
“…At the community level, a significant decrease in mammal, reptile, amphibian, invertebrate and plant species richness has been observed in highly urbanized areas [14]. At the level of individual populations, a broad range of adaptive behavioural, morphological and physiological responses of urban populations have been reported (reviewed in [15]). For example, the plant species Crepis sancta shows a reduced settling success of dispersing seed types and a significant increase in non-dispersing seed types in urban areas associated with increased habitat fragmentation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…At the community level, a significant decrease in mammal, reptile, amphibian, invertebrate and plant species richness has been observed in highly urbanized areas [14]. At the level of individual populations, a broad range of adaptive behavioural, morphological and physiological responses of urban populations have been reported (reviewed in [15]). For example, the plant species Crepis sancta shows a reduced settling success of dispersing seed types and a significant increase in non-dispersing seed types in urban areas associated with increased habitat fragmentation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the evolutionary ecology of urban ecosystems remains poor because of a paucity of data on the subject [7]. Although there have been relatively few studies, researchers have identified several cases of adaptive phenotypic differentiation between paired urban -rural populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, urbanization also represents a potential source of selection and a new avenue to study evolutionary processes (Donihue and Lambert, 2014;Isaksson, 2015;Alberti et al, 2017;Hendry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%